1981
DOI: 10.1051/rphysap:01981001606027500
|View full text |Cite
|
Sign up to set email alerts
|

Le phénomène de superparamagnétisme

Abstract: 2014 Une revue sur le magnétisme des très petites particules, le superparamagnétisme, est effectuée. Dans l'introduction, un bref historique des mesures mettant en évidence le phénomène et une rapide revue des domaines où son étude peut apporter des renseignements importants sont faits. La première partie est consacrée à la théorie du phénomène. Il est examiné en détail les modèles de Néel et de Brown et comparé les valeurs asymptotiques du temps de relaxation aux valeurs numériques calculées par Aharoni. Des … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0
1

Year Published

1997
1997
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(68 citation statements)
references
References 71 publications
(138 reference statements)
3
64
0
1
Order By: Relevance
“…[79] The relaxation time of the magnetization markedly decreases with decreasing particle size. The magnetization follows the direction of the external field when present, and the coercive force appears to be negligible in contrast to that of permanent magnets.…”
Section: Anisotropy Constantmentioning
confidence: 99%
See 1 more Smart Citation
“…[79] The relaxation time of the magnetization markedly decreases with decreasing particle size. The magnetization follows the direction of the external field when present, and the coercive force appears to be negligible in contrast to that of permanent magnets.…”
Section: Anisotropy Constantmentioning
confidence: 99%
“…This process implies the crossing of an anisotropy energy barrier, and thus the thermal variation of the relaxation time, s, has an activation-like dependence. Following Neel, most authors have assumed a simple exponential temperature dependence for s. For an axial magnetocrystalline anisotropy the following dependence was found: [80m] s = s 0 exp(KV/kT) (6) whereas for a cubic magnetocrystalline anisotropy, [79] assuming a [100] easy magnetization axis and rotation restricted to (100) planes, the following relation has been proposed:…”
Section: Anisotropy Constantmentioning
confidence: 99%
“…From T B measurements for both bcc-Fe and fcc-Co samples embedded in silver matrix which have different radius (2R centered around 4.5 and 2.8 nm, respectively), we can underline that the ratio T B (Fe)/T B (Co) equal to 2.6 is well related to the square particles radius ratio (R 2 (Fe)/R 2 (Co)), certainly because the surface grain anisotropy governs the magnetic local order in such nanoparticles [5].…”
Section: Magnetic and Transport Propertiesmentioning
confidence: 72%
“…The transition metal nanoparticles reveal a particular magnetic state namely the superparamagnetism [5] which can be easely described.…”
Section: Magnetic and Transport Propertiesmentioning
confidence: 99%
“…[1][2][3] In our study on 2CaO-2Si(h-Fe203_5, one of slug materials, the clnsters have been found to be magnetite or maghemite of nano meter size scale, and thus bring superparamagnetism [4,5] into the system at least around room temperature. [3,6] In this case, magnetic Fe cations are present in purely amorphous region surrounding the clusters as well as in the crystallographic clusters.…”
Section: Introductionmentioning
confidence: 99%